What makes a multimodal construction? Evidence for a prosodic mode in spoken English - Lehmann, Claudia (Frontiers in Communication, 2024)
Traditionally, grammar deals with morphosyntax, and so does Construction Grammar. Prosody, in contrast, is deemed paralinguistic. Testifying to the “multimodal turn,” the past decade has witnessed a rise in interest in multimodal Construction Grammar, i.e., an interest in grammatic constructions other than exclusively morphosyntactic ones. Part of the debate in this recent area of interest is the question of what defines a multimodal construction and, more specifically, which role prosody plays. This paper will show that morphosyntax and prosody are two different semiotic modes and, therefore, can combine to form a multimodal construction. To this end, studies showing the independence of prosody for meaning-making will be reviewed and a small-scale experimental study on the ambiguous utterance Tell me about it will be reported on.